Averting a malaria disaster: will insecticide resistance derail malaria control?. Issue 10029 (23rd April 2016) - Hemingway, Janet; Ranson, Hilary; Magill, Alan; Kolaczinski, Jan; Fornadel, Christen; Gimnig, John; Coetzee, Maureen; Simard, Frederic; Roch, Dabiré K; Hinzoumbe, Clément Kerah; Pickett, John; Schellenberg, David; et al.
Summary: World Malaria Day 2015 highlighted the progress made in the development of new methods of prevention (vaccines and insecticides) and treatment (single dose drugs) of the disease. However, increasing drug and insecticide resistance threatens the successes made with existing methods. Insecticide resistance has decreased the efficacy of the most commonly used insecticide class of pyrethroids. This decreased efficacy has increased mosquito survival, which is a prelude to rising incidence of malaria and fatalities. Despite intensive research efforts, new insecticides will not reach the market for at least 5 years. Elimination of malaria is not possible without effective mosquito control. Therefore, to combat the threat of resistance, key stakeholders need to rapidly embrace a multifaceted approach including a reduction in the cost of bringing new resistance management methods to market and the streamlining of associated development, policy, and implementation pathways to counter this looming public health catastrophe.